Semantic and grammatical connections of the Old Turkic word аčïγ with the vocabulary of the Kazakh language - Zifa Temirgazina; Olga Andryuchshenko (Turkic Studies Journal)
The article examines the semantic connections of the Old Turkic word аčïγ, which is part of the main lexical fund of the language, with the words of the Kazakh language, genealogically ascending to the Old Turkic word. The lexeme ačïγ denotes a basic taste and is derived from the verb ačï- following a word-formation pattern with the suffix -g, which forms deverbal nouns. The reconstruction of the semantic structure of the polysemous Old Turkic word enables to conclude that it is largely preserved in the modern Turkic languages. This is confirmed by data from Kazakh language dictionaries. The analysis of the semantic structure of the word ačïγ, its comparison with the semantics of the verbal root from which it is derived in Old Turkic, as well as with the semantic structure of the lexeme ащы in Kazakh, has made it possible to identify a number of trends in the development of lexical and grammatical connections between polysemous words in Old Turkic and Kazakh. These include the expansion of direct meanings, the divergence of lexical-semantic variants of the polysemous Old Turkic word, and the emergence of homonyms in the modern Turkic language, such as Kazakh. A simplification of the semantic structure of lexemes etymologically related to the Old Turkic word is also observed, due to the aforementioned process of divergence in lexical-semantic variants, along with the simultaneous emergence of new meanings. An important role in the semantic development of the word ащы in the Kazakh language was played by the syncretism of Old Turkic deverbal words, which led to the differentiation of meanings between adjectives and nouns that were originally part of a single semantic structure of the Old Turkic lexeme. The analysis of the semantic structure of Old Turkic lexemes, as demonstrated by our study, reveals hidden and lost semantic connections in Kazakh words and reconstructs the logic behind the development of their meanings.